Pengaruh Permainan Kecil Dalam Pemanasan Pembelajaran penjas Terhadap Tingkat Kebugaran Jasmani Siswa Tunagrahita - Supriyana, Rivan; Yuda, Aria Kusuma; Dimyati, Akhmad (Jurnal Porkes, 2022)
Small games in the warm-up of physical education learning will be more interesting and fun, because students will be brought to play and in that way the movement needs of mentally retarded students will be met. This study aims to determine the effect of small games in warming up physical education learning on the level of physical fitness of mentally retarded students. In this study, the method used is an experimental research method with one group pretest posttest design. The subjects of this study were mentally retarded students at SMALB-C Tunas Harapan. The sample used in this study amounted to 12 students using a total sampling technique. The instrument used in this study was a physical fitness test with a categorization that was adapted to mentally retarded students aged 16-19 years. Based on the results of data analysis showed an increase in the physical fitness of SMALB-C Tunas Harapan students. This is evidenced by the results of the calculation of the value of t count > t table which is 2.803 > 2.201. From the results of the mean/mean pretest and posttest, it is known that the average pretest is 5.92 and the posttest average is 6.33, an increase of 0.41 or if the percentage is 7%. So, in conclusion, there is an effect of small games in warming up physical education learning on the level of physical fitness of SMALB-C Tunas Harapan students.